2021
DOI: 10.3389/fpsyt.2021.737389
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Related Nuclear Gene Expression in the Nucleus Accumbens and Blood Mitochondrial Copy Number After Developmental Fentanyl Exposure in Adolescent Male and Female C57BL/6 Mice

Abstract: The potency of the synthetic opioid fentanyl and its increased clinical availability has led to the rapid escalation of use in the general population, increased recreational exposure, and subsequently opioid-related overdoses. The wide-spread use of fentanyl has, consequently, increased the incidence of in utero exposure to the drug, but the long-term effects of this type of developmental exposure are not yet understood. Opioid use has also been linked to reduced mitochondrial copy number in blood in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 118 publications
(178 reference statements)
0
8
0
Order By: Relevance
“…Four 14-gauge NAc tissue punches per mouse were collected 24 h after the last social interaction and stored at −80°C until processing. RNA was extracted as described previously ( Calarco et al, 2021 ) with TRIzol (Invitrogen; #15596018) and the EZNA MicroElute Total RNA kit (Omega Bio-Tek, Norcross, GA, United States; #R6831-01) with a DNase step (Qiagen, Germantown, MD, United States; #79254). RNA concentration and quality were determined with a NanoDrop 1000 spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Four 14-gauge NAc tissue punches per mouse were collected 24 h after the last social interaction and stored at −80°C until processing. RNA was extracted as described previously ( Calarco et al, 2021 ) with TRIzol (Invitrogen; #15596018) and the EZNA MicroElute Total RNA kit (Omega Bio-Tek, Norcross, GA, United States; #R6831-01) with a DNase step (Qiagen, Germantown, MD, United States; #79254). RNA concentration and quality were determined with a NanoDrop 1000 spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial copy number were found to be reduced in blood samples of patients with opioid use disorder; however, the link between changes in the reward neural circuitry and the peripheral measurements remains unclear [321]. No clinical study was found regarding KYNs in patients with SUDs.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…The mitochondrial copy numbers were found to be reduced in blood samples of patients with opioid use disorder; however, the link between changes in the reward neural circuitry and the peripheral measurements remains unclear [ 354 ]. No clinical study was found regarding KYNs in patients with SUDs.…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%